The Correlation Between Students’ Comprehension of the Human Movement System and Their Attitudes Toward Maintaining Bone and Joint Health - Sya’adah, Wildatus; Nurlim, Risma; Hafsah (Aspirasi Masyarakat Intelektual Islam Nusantara, 2025)
This study examines the correlation between students’ comprehension of the human movement system and their attitudes toward maintaining bone and joint health among XI MIPA students at MA Wahid Hasyim Balung Jember. Using a quantitative correlational research design, data were collected through multiple-choice tests measuring students’ comprehension and Likert-scale questionnaires assessing their attitudes. A total of 66 students participated in the study, with data analyzed using Spearman’s rank correlation test. The findings indicated that students had a high level of comprehension, with 77% achieving a very high category and 11% classified as high. However, their attitudes toward bone and joint health were predominantly moderate, with 74% in the medium category and only 24% in the high category. Statistical analysis revealed no significant correlation between comprehension and attitude, as evidenced by a correlation coefficient of -0.056 and a p-value of 0.653 (p > 0.05). These results suggest that despite possessing strong cognitive understanding, students do not necessarily translate their knowledge into proactive health behaviors. The findings highlight the need for educational strategies that bridge the gap between theoretical knowledge and practical application, encouraging students to adopt healthier behaviors.